Density and porosity optimization of graphene monoliths with high mass‐loading for high‐volumetric‐capacitance electrodes. Issue 4 (8th August 2022) - Wang, Dongliang; Sheng, Lizhi; Jiang, Meihui; Jin, Xin; Lin, Xinru; Lee, Sang‐Young; Shi, Junyou; Chen, Wenshuai
Abstract: Improving the volumetric capacitance of graphene materials for supercapacitors without sacrificing their rate capability, especially at high mass‐loading, is a challenge because of the sluggish electrochemical kinetics of compact graphene electrodes. Here, a compact graphene monolith (dense graphene ribbons [DGRs]‐0.6) was fabricated by using graphene oxide ribbons as building blocks and deliberately harmonizing the graphene primitive unit structure and interlayer spacing. The DGRs‐0.6 contained abundant oxygen‐containing functional groups and a highly interconnected pore structure, resulting in a large ion‐accessible surface area, a high packing density, and fast electron/ion transport pathways. The DGRs‐0.6 electrode exhibited a volumetric capacitance of 316 F cm –3, a rate capability of 220 F cm –3 at 100 A g –1, and ultralong cycling stability. For a mass loading of 11 mg cm −2, the DGRs‐0.6 delivered volumetric capacitances of 150 F cm −3 at 1 A g −1 and 109 F cm −3 at 50 A g −1 . The good rate capability and volumetric capacitance of DGRs‐0.6 under high mass loading demonstrate its potential as a supercapacitor electrode for practical applications. Abstract : Compact graphene ribbon monoliths with high packing density, specific surface area, and porosity are designed and prepared. The advantageous structures of the compact graphene ribbon monolith contribute to its high volumetric capacitance and high‐rate capability under various mass loadings.